An exploration of the factors which promote and impede correctional supervision on effectiveness with regard to juvenile or young off enders - Clarke-McLeod , PG; Van Zyl, C (Social Work/Maatskaplike Werk, 2002)
Youth crime is increasing at an alarming rate and imprisonment as the only measure of punishment has become a contentious issue for the South African Correctional Services. The 1992 campaign "Justice for the children: No child should be caged" raised national and international awareness about young people at risk in. In the words of Ruth Morris: Prisons are not the greatest. They breed bitterness and crime, destroy people who work and live in them and it’s not nice to cage your fellow human beings. Prisons cost more than the best university education, while giving appalling results ( 1993 (1) SA 476). The question that needs to be asked is whether imprisonment really does give effect to punitive motives of deterrence, retribution, protecting the community and rehabilitation of the offender. The introduction of correctional supervision as a sentencing option has ushered in a new phase in our criminal justice system. Th South African model of correctional supervision is described as a community-based sentence that is served within the community and the probationer is subject to stringent conditions such as house arrest, community service, monitoring and the attendance of treatment programmes. The correctional social worker together with the multidisciplinary team has a cardinal role to play in the treatment of the young offender. The various professions with their expertise have a major role to play in the treatment programmes geared to assist the young offender to reintegrate and function positively in the community.